Effects of Tm3+ concentration on upconversion luminescence and temperature‐sensing behavior in Tm3+/Yb3+:Y2O3 nanocrystals. (3rd September 2018) - Chen, Guangrun; Lei, Ruoshan; Huang, Feifei; Wang, Huanping; Zhao, Shilong; Xu, Shiqing
Abstract: The effects of Tm 3+ concentration on upconversion emission and temperature‐sensing behavior of Tm 3+ /Yb 3+ :Y2 O3 nanocrystals were investigated. Blue and red emissions were observed under 980 nm excitation. Both upconversion emissions and the blue to red intensity ratio were found to decrease with increasing Tm 3+ concentration. The temperature‐sensing performances of the samples were studied, the fluorescence intensity ratio of 1 G4(a) → 3 H6 (477 nm) and 1 G4(b) → 3 H6 (490 nm) transitions from Tm 3+ ions was chosen as the thermometric index. The results showed that the sensor sensitivity was sensitive to Tm 3+ ion concentration. The maximum sensitivity of ~32 × 10 −4  K −1 was obtained for 0.1%Tm 3+ /5%Yb 3+ :Y2 O3 nanocrystals at 344 K. Moreover, a marked optical induced heating effect was also found in the nanocrystals. The prepared Tm 3+ /Yb 3+ :Y2 O3 nanocrystals could be used in temperature‐sensing probes and in optical heaters.